DEVELOPMENT OF ENGLISH BIG BOOK TO TEACH VOCABULARY FOR EIGHTH-GRADE STUDENTS Nur Hidayah1) , Tyas Alhim Mubarak 2) , Widiarin - Nur Hidayah Nur Hidayah; Tyas Alhim Mubarok; Widiarini Widiarini (Journey: Journal of English Language and Pedagogy, 2023)
The purpose of this study is to develop learning media in the form of recount text big books and to determine the feasibility of the media. This research was conducted on class VIII students of SMP Islam Mamba'ul Jadidi. The research method used is Research and Development (RandD) which uses the ADDIE model. The steps are (1) needs analysis, (2) product development, (3) product design, (4) product implementation, and (4) product evaluation. Validation by experts is used to determine the eligibility of the media. Researchers then do product testing. based on research (1) the media expert validator gets a score of 94% (2) the material expert validator gets a score of 98%. (3) The language validator got a score of 95%. Student vocabulary assessment got a score of 88%. Evaluation of student assessment responses to the media score of 89%. Thus the media is accepted by students. Research and development work produces a ledger that is suitable for use